Shape design of channels and manifolds in a multichannel microreactor using thermal-fluid compartment models - Tonomura, Osamu; Noda, Masaru; Hasebe, Shinji (Frontiers in Chemical Engineering, 2022)
In the design of microreactors, the shape as well as the size is an important design factor for achieving high performance. Recent advances in computational fluid dynamics (CFD) enable us to know flow and temperature distributions in microreactors of various shapes and sizes without conducting experiments. However, it is often important to develop a simpler model than CFD to further reduce the computational time required for reactor design with iterative performance evaluations. In this research, a thermal-fluid compartment model-based approach is proposed for basic design of a multichannel microreactor. The proposed approach consists of two parts, i.e., thermal design and fluid design. In the thermal design part, two types of thermal compartments, which are used to discretize a reaction channel surrounded by wall and describe the mass and heat balances over the channel, are developed to optimize the channel shape. In the fluid design part, three types of fluid compartments, which are used to discretize the reactor and describe the mass and pressure balances over the reactor, are introduced to optimize manifold shape. The proposed approach is applied to a design problem and the results show that microchannels and manifolds with varying width are effective in realizing the uniform temperature and flow distributions, respectively. In addition to the proposed design approach, a transfer function-based compartment model is developed to estimate the residence time distribution of fluid in a microreactor without running time-dependent CFD simulation.